An environmental scan of academic pediatric emergency medicine at Canadian medical schools: Identifying variability across Canada. Issue 5 (28th January 2018) - Artz, Jennifer D.; Meckler, Garth; Argintaru, Niran; Lim, Roderick; Stiell, Ian G.
ABSTRACT: Objective: To complement our environmental scan of academic emergency medicine departments, we conducted a similar environmental scan of the academic pediatric emergency medicine programs offered by the Canadian medical schools. Methods: We developed an 88-question form, which was distributed to pediatric academic leaders at each medical school. The responses were validated via email to ensure that the questions were answered completely and consistently. Results: Fourteen of the 17 Canadian medical schools have some type of pediatric emergency medicine academic program. None of the pediatric emergency medicine units have full departmental status, while nine are divisions, two are sections, and three have no status. Canadian academic pediatric emergency medicine is practised at 13 major teaching hospitals and one specialized pediatric emergency department. There are 394 pediatric emergency medicine faculty members, including 13 full professors and 64 associate professors. Eight sites regularly take pediatric undergraduate clinical clerks, and all 14 provide resident education. Fellowship training is offered at 10 sites, with five offering advanced pediatric emergency medicine fellowship training. Half of the sites have at least one physician with a Master's degree in education, totalling 18 faculty members across Canada. There are 31 clinical researchers with salary support at nine universities. Eleven sites have published peer-reviewed papers ( n =423) in the past five years, ranging from two to 102 per site. Annual academic budgets range from $10, 000 to $2, 607, 515. Conclusions: This comprehensive review of academic activities in pediatric emergency medicine across Canada identifies the variability across the country, including the recognition of sites above and below the national average, which may prompt change at individual sites. Sharing these academic practices may inspire sites to provide more support to teachers, educators, and researchers. RÉSUMÉ: Objectif: Afin de compléter l'analyse environnementale des départements universitaires de médecine d'urgence, nous avons procédé au même type d'analyse que la précédente mais, cette fois, pour les programmes universitaires de médecine d'urgence pédiatrique (MUP), offerts par les écoles de médecine au Canada. Méthode: Nous avons élaboré un formulaire comptant 88 questions, qui a été distribué aux responsables de l'enseignement de la médecine d'urgence pédiatrique dans chacune des écoles de médecine. Les réponses ont été validées par courriel afin de nous assurer de leur cohérence et de leur caractère complet. Résultats: Sur les 17 écoles de médecine au Canada, 14 offrent une forme quelconque de programme universitaire de MUP. Toutefois, aucune des unités de MUP ne jouit du titre de département à part entière; ainsi, neuf unités sont reconnues comme des divisions et deux, comme des sections, tandis que trois n'ont aucun titre officiel. La MUP universitaire se pratique dans treize grands hôpitaux d'enseignement et dans un service spécialisé en MUP. Le corps enseignant compte 394 membres en MUP, dont 13 professeurs titulaires et 64 professeurs agrégés. Dans huit universités, on accepte normalement les stagiaires cliniques de premier cycle en pédiatrie, et les quatorze écoles offrent de la formation au niveau de la résidence. Une formation postdoctorale est donnée dans dix écoles, et cinq d'entre elles fournit une formation spécialisée en MUP. On compte au moins un médecin ayant une maîtrise en éducation dans la moitié des établissements, ce qui porte à 18 leur nombre total au Canada. Trente et un cliniciens-chercheurs reçoivent une aide salariale dans neuf universités. Des articles évalués par les pairs (n=423) ont été publiés dans onze écoles au cours des cinq dernières années, et le nombre varie de 2 à 102 dans chacune d'elles. Enfin, les budgets annuels consacrés à l'enseignement de la MUP varient de 10 000 $ à 2 607 515 $. Conclusion: Cet examen complet des activités universitaires en MUP, mené à la grandeur du pays fait ressortir des différences entre les écoles de médecine au Canada, notamment le classement de celles qui se situent au-dessus ou au-dessous de la moyenne nationale, ce qui peut susciter des changements au sein des écoles elles-mêmes. Ainsi, le fait de porter à la connaissance des autres les pratiques universitaires peut inciter les écoles à donner plus de soutien aux enseignants, aux médecins-enseignants et aux chercheurs.